ULTRASTRUCTURAL CHANGES INDUCED BY IMIDACLOPRID IN MALE ALBINO RATS - S.SOUJANYA (International Journal of Pharma and Bio Sciences, 2013)
In the present study, ultrastructural alterations induced by oral administration of imidacloprid over 4 weeks was assessed in rats. Forty eight male sprague dawley rats procured from NIN and divided into four groups. Group 1 given with basal diet, group 2 orally gavaged with 80mg/kg/day imidacloprid, group 3 was treated with vitamin C at the rate of 10 mg/kg b.wt/day and group 4 was treated with both imidacloprid and vitamin C for 4 weeks. In group 2, Ultra thin sections of kidney has evidenced apoptotic nuclei, pleomarphic mitochondria and liver showed swollen nuclei, disrupted chromatin and rough endoplasmic reticulum. Testes revealed increased perinuclear space, disintegrated chromatin, degeneration of spermatids and brain revealed vacuolar mitochondria and apoptotic nuclei. A mild improvement was observed in group 4. In conclusion, these results suggest that exposure to imidacloprid in rats induced ultrastructural alterations and co-administration of vitamin C brought mild protection.